Supply Chain - Sustainability Index- An Approach towards Benchmarking Parameters for the Food Industry - Papri Ray; R Duraipandian; Hari Om Harsh (International Journal of Supply Chain Management, 2021)
Despite the optimistic outlook at the economy, the food industry has its share of shortcomings in the forefront of sustainable operations. SMEs have resource constraints such as inefficient data handling capacity, insufficient financial support and transparency issues. However, the major problem that must be addressed is the lack of ‘technical know-how’ about metric for measuring sustainability performance. The approach is based on the study of Global Reporting Initiatives (GRI) and Dow Jones Sustainability Indices (DJSI) to design parameters based on people, planet and profit indicators. In a global perspective, 25 organizations (small, medium and large enterprises) in the food industry are selected and data collection is carried out from sources like ‘Sustainability report’ and ‘Annual report’ of these organisations. Data Envelopment Analysis (DEA), is used to arrive at the relative efficiency scores and it is taken as input to the SISO (single input single output) type Fuzzy Model to arrive at an index. A case simulation to demonstrate the application, DMU with relative efficiency score of 34% was taken as input which resulted to output on sustainability index of 2 (on a scale of 1-5) indicating poor sustainability of the organisation. A unique work based on parameter design for selecting the performance measure of sustainability and arriving at index is not discussed in the present research. The approach provides a tool to measure the sustainability performance for the organisation.